ANALISIS RASIO KEUANGAN UNTUK MENILAI EFEKTIVITAS DAN EFISIENSI ANGGARAN PENDAPATAN DAERAH PADA DINAS PENDAPATAN DAERAH KABUPATEN BANYUASIN - masayu mikial (JURNAL KOMPETITIF, 2012)
Formulation of the problem in this study is whether the Revenue Budget at the Department of Revenue District Banyuasin been effective and efficient. The aim is to assess the effectiveness and efficiency of budget revenues in Banyuasin District Revenue Office. Research conducted includes descriptive studies, where the goal is to present a structured, factual and accurate facts about the financial ratio analysis of Department of Revenue. Variables to be analyzed in this study is to explain financial ratios, Revenue Budget, effectiveness, and efficiency, where the variables will be measured by the ratio scale. Analysis conducted in this study was to assess the effectiveness and efficiency in the realization of revenue by using an analytical tool that is the ratio of self-sufficiency ratio, the ratio of effectiveness, consistency ratio, Debt Service Coverage Ratio, and growth ratios.Based on the results of research and analysis has been carried out concluded that the District Revenue Office Banyuasin been able to realize the revenue budget of the region, because its terms are met and the assessment of the effectiveness and efficiency is good enough Analysis conducted in this study was to assess the effectiveness and efficiency in the realization of revenue by using an analytical tool that is the ratio of self-sufficiency ratio, the ratio of effectiveness, consistency ratio, Debt Service Coverage Ratio, and growth ratios. Based on the results of research and analysis has been carried out concluded that the District Revenue Office Banyuasin been able to realize the revenue budget of the region, because its terms are met and the assessment of the effectiveness and efficiency is good enough Key words: financial ratio, budget, Effectiveness and EfficiencyÃ‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â Ã‚Â